2009
DOI: 10.1556/aagr.57.2009.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Role of salicylic acid in regulation of cadmium toxicity in wheat ( Triticum aestivum L.)

Abstract: Treatment with CdCl 2 (0, 100, 400 and 1000 µM) resulted in the inhibition of root dry biomass and root elongation and to increased Cd accumulation in the roots. These treatments also decreased the relative water content, chlorophyll content, 14 CO fixation, phosphoenol pyruvate carboxylase and ribulose-1,5-bisphosphate carboxylase activity and abscisic acid (ABA) content, while increasing the malondialdehyde, hydrogen peroxide and free proline contents and causing changes in the chloroplast and root ultrastru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
1
6
0
1
Order By: Relevance
“…5), which indicated that the free radical formation was stimulated by Cd toxicity, generating serious lipid peroxidation and leading to plasma membrane injury. Similar results were reported in Triticum aestivum L. (Moussa and El-Gamal 2010) and Brassica juncea (Kaur et al 2019) plants. However, application of ACh under Cd stress resulted in decrease of MDA content.…”
Section: Discussionsupporting
confidence: 89%
“…5), which indicated that the free radical formation was stimulated by Cd toxicity, generating serious lipid peroxidation and leading to plasma membrane injury. Similar results were reported in Triticum aestivum L. (Moussa and El-Gamal 2010) and Brassica juncea (Kaur et al 2019) plants. However, application of ACh under Cd stress resulted in decrease of MDA content.…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, studies of ABA-deficient and ABA-insensitive mutants of Arabidopsis excluded a direct mediatory role for ABA in Cd-imposed phytotoxic effects on germination and growth assays (Sharma and Kumar, 2002 ). A decrease in ABA content has also been observed in wheat plants treated with 400 and 1000 μ M of CdCl 2 (Moussa and El-Gamal, 2010b ).…”
Section: Plant Growth Regulatorsmentioning
confidence: 83%
“…For example, it was reported that treatment of Cd-stressed plants with salicylic acid alleviates a number of effects caused by Cd. It is likely that the positive effects of salicylic acid are not directly correlated with the removal of Cd, but with the activation of response and defense genes, which in turn may code for enzymes involved in the maintenance of homeostasis of plant cells ( Moussa and El-Gamal, 2010 ). Activation of pathogenesis-related defense proteins of the glucanase family is likely to be a common trait of many plants in response to Cd.…”
Section: Other Factors Affecting the Response/adaptation/defense Of Pmentioning
confidence: 99%